The Role of the Superior Cervical Sympathetic Ganglion in Ischemia Reperfusion-Induced Acute Kidney Injury in Rats - Zhang, Wencui; Li, Zhen; Li, Zhixiao; Sun, Tianning; He, Zhigang; Manyande, Anne; Xu, Weiguo; Xiang, Hongbing (Frontiers in Medicine, 2022)
Acute kidney injury (AKI) has been found to be a serious clinical problem with high morbidity and mortality, and is associated with acute inflammatory response and sympathetic activation that subsequently play an important role in the development of AKI. It is well known that the sympathetic nervous system (SNS) and immune system intensely interact and mutually control each other in order to maintain homeostasis in response to stress or injury. Evidence has shown that the superior cervical sympathetic ganglion (SCG) participates in the bidirectional network between the immune and the SNS, and that the superior cervical ganglionectomy has protective effect on myocardial infarction, however, the role of the SCG in the setting of renal ischemic reperfusion injury has not been studied. Here, we sought to determine whether or not the SCG modulates renal ischemic reperfusion (IR) injury in rats. Our results showed that bilateral superior cervical ganglionectomy (SCGx) 14days before IR injury markedly reduced the norepinephrine (NE) in plasma, and down-regulated the increased expression of tyrosine hydroxylase (TH) in the kidney and hypothalamus. Sympathetic denervation by SCGx in the AKI group increased the level of blood urea nitrogen (BUN) and kidney injury molecule-1 (KIM-1), and exacerbated renal pathological damage. Sympathetic denervation by SCGx in the AKI group enhanced the expression of pro-inflammatory cytokines in plasma, kidney and hypothalamus, and increased levels of Bax in denervated rats with IR injury. In addition, the levels of purinergic receptors, P2X3R and P2X7R, in the spinal cord were up-regulated in the denervated rats of the IR group. In conclusion, these results demonstrate that the sympathetic denervation by SCGx aggravated IR-induced AKI in rats via enhancing the inflammatory response, thus, the activated purinergic signaling in the spinal cord might be the potential mechanism in the aggravated renal injury.